Assessing Career Barriers of Samoan Women: The Intersectionality of Race and Fa'aSamoa - Ofe-Grant, Betty (Human Resources New Zealand (HRNZ), 2024)
Little is known about the career experiences of Samoan women working in New Zealand within the sociopolitical context of fa’a Samoa (Samoan culture). Although gender and race have been shown to impact careers, it is unclear how Samoan women negotiate and make sense of their identities against this backdrop. Using intersectionality, fa’a Samoa and Teu le va methodology, this study explored the experiences of 16 Samoan women in senior management. Participants reported gender bias, racism, and cultural exclusion perpetrated by White New Zealanders, and Samoan and Pacific men. Career strategies included building alliances with unions, diversity groups, and other bi-racial colleagues that advocate for gender and race equality; confronting and reporting incidents of discrimination; mentorship with White New Zealand mentors; and prioritising work over negative thoughts and experiences. This study provides exclusive insights into the career complexities of Samoan women in managerial careers and the intersecting challenges perpetuating inequality. HR and management implications highlight the need to recognise intersectionality
Keywords: Career barriers; fa'aSamoa; gender bias; intersectionality; racism; Samoans; 1503 Business and Management; 1599 Other Commerce, Management, Tourism and Services; 3505 Human resources and industrial relations; 3507 Strategy, management and organisational behaviour; 5201 Applied and developmental psychology